A non-target screening study of high-density polyethylene pipes revealed rubber compounds as main contaminant in a drinking water distribution system. (1st February 2023) - Diera, Tomas; Thomsen, Anne Holm; Tisler, Selina; Karlby, Lone Tolstrup; Christensen, Peter; Rosshaug, Per Sand; Albrechtsen, Hans-Jørgen; Christensen, Jan H.
HIghlights: Migration revealed 133 VOC and semi-VOC compounds originating from HDPE pipes. A library containing 274 compounds detected in PE is provided. Compounds detected in field study analysis of drinking water assigned to the sources. The most pronounced compounds in the drinking water were rubber related. The field study found PE-related antioxidants and degradation products with low intensities. Abstract: Polyethylene (PE) pipes are often the material of choice for water supply systems, thanks to their favorable properties, such as high strength-density ratio and corrosion resistance. However, previous studies have shown that organic compounds can migrate from PE pipes to the water. This study aimed to identify potential organic compounds migrating from high-density PE (HDPE) pipes used to distribute drinking water in Denmark, based on laboratory experiments and sampling in the distribution system using a two-tiered study design. In the first tier, migration of volatile and semi-volatile organic compounds (VOCs and semi-VOCs) from HDPE pipes were investigated over one, three, and nine days in laboratory experiments, performed according to modified standards for migration testing (EN 12, 873–1). The analytical workflow consisted of solid-phase extraction (SPE) for 10, 000 times enrichment and gas chromatography – mass spectrometry (GC–MS) analysis from the water phase after migration. A total of 133 compounds originating from the PE pipes were detected. Thirty-one compounds were detected by suspect screening (SS), while the remaining 102 compounds were detected by non-target screening (NTS) analysis. Among the detected compounds were also hindered amine stabilizers (HALS), flame retardant, and plasticizer tris(2-chloroethyl) phosphate. In the second tier, drinking water from a water distribution system in Copenhagen, Denmark, with a newly installed HDPE pipe was sampled and analyzed with GC–MS and liquid chromatography high-resolution mass spectrometry (LCHRMS). A total of 51 compounds were detected in the water, 12 of which were assigned to migration from HDPE. Surprisingly, HDPE antioxidants and their degradation products contributed only a relatively small percentage of the total measured compound intensities in the drinking water distribution system. Instead, a larger proportion of the compounds detected were assigned to rubber seals, used upstream in the water system from the abstraction site to delivery at the consumer tap. Seals are considered trifle in the larger picture of materials in contact with drinking water, however these results may cause a reconsideration of this position. Graphical abstract: Image, graphical abstract